Adjustment of total activity as a response to handicapping European starlings during parental care. (February 2019) - Serota, Mitchell W.; Williams, Tony D.
Abstract : Parental care is widely assumed to be costly, and life-history theory predicts that individuals that invest more in parental care should benefit in terms of number of offspring produced but that increased parental care might come at a cost in terms of decreased future fecundity and/or survival. However, the notion that parents that work 'harder', commonly measured by the rate at which parents visit the nestbox to provision their chicks, produce more, fitter chicks is surprisingly poorly supported. One potential reason for this apparent lack of relationship between measured workload during parental care and breeding productivity is that nest visit rate does not provide a good measure of foraging effort. Here, we used an automated radiotelemetry system to measure activity of individual female European starlings, Sturnus vulgaris, during breeding, combined with a handicapping experiment (combination of radiotransmitters and wing clipping) and measures of foraging metrics, current breeding productivity, future fecundity and return rate. Handicapping decreased current breeding success due to higher abandonment and nest failure, but among successful birds (fledging ≥ 1 chick) there was no effect of handicapping on brood size at fledging for the current breeding attempt. Handicapping decreased future fecundity, the probability of initiating a second brood, and return rate, but there was no evidence for additive costs of reproduction in wing-clipped females. Handicapping had no effect on provisioning rate but automated tracking data showed that, during chick rearing, wing-clipped females had 22% lower activity compared to females with radios only. Our data provide an explanation for the often contradictory effects of handicapping reported on reproductive effort and costs of reproduction: individuals can use behavioural flexibility – decreasing overall activity while maintaining provisioning rate – along with changes in mass and nestling diet to mitigate putative effects of increased workload imposed by handicapping. Highlights: We studied effects of wing clipping on breeding female starlings. Handicapping decreased current and future breeding success. There was no evidence for an additive cost of reproduction between handicapped groups. Wing-clipped females had 22% lower activity than females with radios only. Wing-clipped females adjusted activity and foraging behaviour to mitigate effects.